Relationship Knowledge And Attitude Towards Stunting Prevention In Adolescent Girls - Adriani, Prasanti; Lanti Retno Dewi, Yulia; Setyowati, Retno; Sugihardjo, Sugihardjo (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
Indonesia possesses the second highest prevalence of stunting globally, surpassed only by Cambodia. Stunting is a pervasive problem that impacts not only infants and expectant mothers but even teenagers. Teenage females should be educated about the perils of stunting, including its indications, and the most effective strategies to prevent it by adopting healthful eating habits. Ensuring that adolescent girls do not develop anemia is a vital first measure in effectively avoiding stunting. The prevalence of stunted growth among babies and the occurrence of early marriages remain significantly high in Purbalingga Regency. Adolescents must improve their understanding and reproductive health in order to prevent stunting. The objective of this study is to investigate the correlation between the knowledge and attitudes of teenage girls in the Purbalingga Regency region about the prevention of stunting. This study employs a quantitative research design, a cross-sectional method, with a sample size of 75 female adolescents in Senior High School. The research findings demonstrate a robust correlation between the level of knowledge and the attitudes of teenage females in the context of preventing stunting. The correlation coefficient value of 0.675 and the significance value of 0.000, which is less than 0.01, clearly indicate this.